Binswanger's disease and quantitative fractional anisotropy Doença de Binswanger e anisotropia fracionada quantitativa - Eliasz Engelhardt; Denise Madeira Moreira; Gilberto Sousa Alves; Maria Elisa Oliveira Lanna; Carlos Eduardo de Oliveira Alves; Letice Ericeira-Valente; Felipe Kenji Sudo; Jerson Laks (Arquivos de Neuro-Psiquiatria)
OBJECTIVE: To study the integrity of the white matter in Binswanger's disease (BD) patients with quantitative fractional anisotropy (DTI-FA). METHOD: Controls (12) and patients with BD (12) were included. Scans performed with MR (GE Signa Horizon/1.5T). Fazekas's score=6 with white matter hyperintensities extension >75% assessed on FLAIR scans. Standard parameters for DTI-FA were used. ROIs placed in symmetrical regions on two axial planes, data pooled in anterior (frontal) and posterior (temporo-parieto-occipital) regions. Analysis with Functool. Statistics for anterior and posterior regions comparison. RESULTS: DTI-FA showed reduction of anisotropy, reflecting axonal damage and demyelination of fibers, more prominent in anterior in relation to posterior region, in BD patients in comparison to controls. CONCLUSION: Loss of integrity of fiber tracts reflects interruption of neural networks that subserve cognitive, behavioral, and motor integration. The more severely affected frontal region is related to executive dysfunction, a characteristic feature of Binswanger's disease. OBJETIVO: Estudar a integridade da substância branca em pacientes com doença de Binswanger (DB) com anisotropia fracionada quantitativa (DTI-FA). MÉTODO: Incluídos controles (12) e pacientes com DB (12). Obtidas imagens de RM (GE Signa Horizon/1,5T). Escore=6 de Fazekas com hiperintensidades da substância branca com extensão >75% avaliados em imagens em FLAIR. Utilizados parâmetros padrão para DTI-FA. ROIs colocados em regiões simétricas de dois planos axiais, dados das regiões anterior (frontal) e posterior (têmporo-parieto-occipital) reunidos. Análise com Functool. Estatística para comparar regiões anteriores e posteriores. RESULTADOS: DTI-FA mostrou redução da anisotropia, refletindo lesão axonal e desmielinazação de fibras, com predomínio na região anterior em relação à posterior, nos pacientes com DB em comparação aos controles. CONCLUSÃO: Perda da integridade de feixes de fibras reflete interrupção de redes neurais subjacentes à integração cognitiva, comportamental e motora. A região frontal, mais gravemente atingida, está relacionada à disfunção executiva, aspecto característico da doença de Binswanger.